La relative en pepel - Ndao, Dame (AAeO - Afrikanistik-Aegyptologie-Online, 2015)
This article is about the basis of different ways used by pepel language to describe relativity. The language distinguishes two types of functioning manners. The first strategy is marked by the presence of a relativisor placed after the verb including a nominal class. The second strategy is recognized by a morphem placed between the antecedent and the relative. As all the arguments are relativisable in pepel, I will do my best to investigate one case after another the relativisation of the subject, then that of the object befor ending with the relativisation of circumstants.